Bad apples identify, prevent & manage negative behavior at work - Furnham, Adrian (New York Palgrave Macmillan, 2011)
In a difficult economic climate it is more important than ever to manage bad behaviour in the workplace and minimize the damage negative and destructive employees can have on an organization. This book looks at the problems companies can face but also shows how to resolve these issues and work towards a positive outcome.
Includes bibliographical references (p. 282-295) and index.
Keywords: Problem employees